Implementation of Human Resources in the Management of Abadi Aisyiyah Orphanage, Tangerang City - Aries Sundoro; Nuhfendi; Setiawan, Aries; Sonya Komala, Cantik; Samuel (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
This study aims to analyze the implementation of human resource management in the administration of orphanages and the supporting and hindering factors in managing these institutions. The research used a qualitative approach, with data collection techniques involving observation, interviews, and documentation. The findings indicate that the human resource management applied at the Abadi Aisyiyah orphanage in Tangerang City consists of several steps: job analysis, human resource planning, recruitment, selection, and placement. Additionally, compensation, integration of administrators, and human resource development are key components. Finally, human resource maintenance is also important. Supporting factors include having qualified human resources, the sincerity of the administrators, and community support. The challenges in implementing human resource management include issues with the orphanage’s facilities, funding problems, and limitations in human resources.